Montreal Cognitive Assessment scale in patients with Parkinson Disease with normal scores in the Mini-Mental State Examination - Vásquez, Krisly Arguedas (Dement Neuropsychol, 2019)
Several screening tests have been used for cognitive evaluation in Parkinson’s disease (PD). OBJECTIVE: To evaluate the usefulness of the Montreal Cognitive Assessment (MoCA) in patients with Parkinson’s disease and no cognitive impairment complaints. METHODS: A total of 40 PD patients with no complaints of cognitive problems were included. Patients were selected using the Mini-Mental State Examination (MMSE) and the MoCA was then administered. RESULTS: 80% of patients exhibited Mild Cognitive Impairment (MCI) according to the MoCA. Statistically significant differences in visuospatial, attention and delayed recall functions were evident between the normal and abnormal MoCA groups. CONCLUSION: The study results suggest that MoCA may be a good screening test in patients with PD who do not present cognitive complaints.